Visualization and Forecast for Pollution Death Threats in ASEAN - Axel Wijaya, Kimi; Sunardi Oetama, Raymond (International Journal of Science, Technology & Management, 2023)
Air pollution is a serious problem experienced by all countries because it can cause many health problems and even death. The situation in countries of the Association of Southeast Asian Nations or ASEAN is the high air pollution-related mortality rates, especially in countries like Laos, Myanmar, and Cambodia, which face elevated risks due to poor air quality. Raising public awareness about air pollution requires a concerted effort involving various strategies and channels. The paper provides research findings on air pollution, including data on air pollution-related deaths, regional variations, and forecasting using Tableau software. It underscores the need to address air pollution challenges, particularly in ASEAN, to protect public health. Due to industrialization, ASEAN countries are grouped into high and low mortality clusters and ongoing air pollution challenges in Asia. Continued efforts are needed, especially in Myanmar, Cambodia, the Philippines, and Laos.